Morphological and Anatomical Characteristics of leaves of Ten Soybean (Glycine max L. Merill) Lines. Issue 1 (May 2019) - Julia, N; Zubaidah, S; Kuswantoro, H
Abstract: The characterization of the leaf morphology and anatomy can be useful to determine the superiority of the plant. The purpose of this study was to observe and analyze the morphological and anatomical leaves characteristics of the 10 soybean lines. The experiment employed a randomized block design with three replications. The results showed that the highest scores of the leaf length, leaf width, leaf thickness, petiole length, and petiole diameter could be observed in Brg/Myp-3 line. The largest leaf ratio was reported by Anj/MLGG 0511-29, and the lowest scores in the leaf length, leaf width, petiole length, petiole diameter, and leaf ratio were found in MLGG 0892 line. Grb/Lwt-17 and Grb/Myp-25 had the thinnest leaves. Grb/Lwt-12 have the highest number of trichomes, both on the upper and lower surfaces of the leaf, while Grb/Myp-65 had the smallest number. Anj/MLGG 0511-20 and Brg/Myp-14 had the longest trichomes, while Grb/Lwt 17 had the shortest trichomes. The highest number of stomata was recorded in Grb/Lwt-17. The results of the correlation test showed some significant relationships between the leaf characteristics: the length of the leaf and the width of the leaf and the petiole diameter; the length of the upper trichome and the length of the lower trichome, and the width of the upper trichome and the number of the lower stomata.